1980
DOI: 10.1177/003368828001100204
|View full text |Cite
|
Sign up to set email alerts
|

Learner and Teacher Roles in the Treatment of Oral Error in Group Work

Abstract: It is now generally accepted that language learners' errors play a crucial role in both the learning process, by allowing the learner to test his hypotheses s about the target language (TL), and in the teaching process, by supplying the teacher with information about what has or has not been mastered (Corder 1967). This approach to error does not accept the premise that all the learner's errors are due to interference only or that errors should be, where possible, either kept to a minimum or drilled out of exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 5 publications
1
52
1
Order By: Relevance
“…However, although all interlocutor types consistently provided negative feedback, in adult dyads, NSs provided significantly more feedback than NNSs, which at first appears to conflict with earlier studies that found more negotiation when NNSs interacted with other NNSs than when they interacted with NSs (Bruton & Samuda, 1980;Gass & Varonis, 1994;Long & Porter, 1985;Pica et al, 1996;Polio & Gass, 1998;Porter, 1986;Varonis & Gass, 1983. However, as discussed above, our study took the grammaticality of the learners' original utterances into account.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, although all interlocutor types consistently provided negative feedback, in adult dyads, NSs provided significantly more feedback than NNSs, which at first appears to conflict with earlier studies that found more negotiation when NNSs interacted with other NNSs than when they interacted with NSs (Bruton & Samuda, 1980;Gass & Varonis, 1994;Long & Porter, 1985;Pica et al, 1996;Polio & Gass, 1998;Porter, 1986;Varonis & Gass, 1983. However, as discussed above, our study took the grammaticality of the learners' original utterances into account.…”
Section: Discussioncontrasting
confidence: 71%
“…In addition, assessing the feedback provided by NNS interlocutors, in comparison to NSs, may shed light on the value of learner-learner pair work and thus contribute to the design of instructional programs. Previous research has found that NNS±NNS interaction tends to include a higher incidence of interactional features such as prompts and various types of negotiation (when compared to NS±NNS interaction), particularly when the NNSs are at different developmental levels (Bruton & Samuda, 1980, Gass & Varonis, 1994Long & Porter, 1985;Pica et al, 1996;Porter, 1986;Varonis & Gass, 1983. Thus, if one posits, as many do, that a combination of L2 input, interactional feedback, and production opportunities is of crucial importance for L2 learners, at first glance it might seem that NNSs would benefit more from interacting with other NNSs than with NSs.…”
Section: Native Versus Nonnative Interlocutorsmentioning
confidence: 99%
“…There seems to be considerable individual variability in the amount of attention students pay to their own and others' speech, however (Gaies, 1983b;Morrison and Low, 1983), and a suggestion that training students to correct each other can help remedy this (Bruton and Samuda, 1980). During group work, learners seem more apt to repair lexical errors, whereas teachers pay an equal amount of attention to errors of syntax and pronunciation (Bruton and Samuda, 1980). Learners almost never mi §-correct during unsupervised group work (Bruton and Samuda, 1980;Porter, 1983).…”
Section: 34 ~~~~J~dmentioning
confidence: 99%
“…During group work, learners seem more apt to repair lexical errors, whereas teachers pay an equal amount of attention to errors of syntax and pronunciation (Bruton and Samuda, 1980). Learners almost never mi §-correct during unsupervised group work (Bruton and Samuda, 1980;Porter, 1983).…”
Section: 34 ~~~~J~dmentioning
confidence: 99%
“…A similar question as to the wisdom of group activities, given nonnative speakers' level of competence in the L2, has been raised regarding group speaking activities. However, little miscorrection of student speech by peers was reported in studies by Bruton and Samuda (1980), Porter (1983), cited in Long and Porter (1985), and Deen (1988).…”
mentioning
confidence: 99%